Care and cost trajectories of asylum seekers in a nurse-led, patient centered, care network in Switzerland - Jacques Spycher; Patrick Bodenmann; Raphaël Bize; Joachim Marti (BMC, 2021)
Abstract Background Switzerland, with its decentralized health system, has seen the emergence of a variety of care models to meet the complex needs of asylum seekers. A network of public and private providers was designed in the canton Vaud, in which a nurse-led team acts as a first contact point to the health system and provides health checks, preventive care, and health education to this population. In addition, the service plays a case management role for more complex and vulnerable patients. While the network has been examined from a clinical angle, we provide the first descriptive evidence on the care and cost trajectories of asylum seekers in the canton. Methods We used routinely collected administrative, patient-level data in a Swiss region responsible for 10% of the asylum seekers in the country. We extracted data on all asylum seekers aged 18 or older who entered the network between 2012 and 2015. The data covered all healthcare costs during the period until they left the network, either because they were granted residence, they left the country, or until 31 December 2018. We estimated random effects regression models for costs and consultations within and outside the network for each month of stay in the network. We investigated language barriers in access to care by stratifying the analysis between patients who spoke one of the official Swiss languages or English and patients who did not speak any of these languages. Principal findings We found that both overall health care costs and contacts with the nurse-led team were relatively high during the first year of stay. Asylum seekers then progressively integrated into the regular health system. Individuals who did not speak the language generally had more contacts with the network and fewer contacts outside. Conclusions In this exploratory study, we observe a transition from nurse-led specific care with frequent contacts to care in the regular health system. This leads us to generate the hypothesis that a nurse-led, patient-centered care network for asylum seekers can play an important role in providing primary care during the first year after their arrival and can subsequently help them navigate autonomously within the conventional healthcare system.